Critical Appraisal of the Ethical Considerations' Reports in Nursing Studies Published by Iranian Nursing Journals - A Heydari; T Pourghaznein (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: In order to support the rights of the human subjects and to prevent their exposure to the probable risks arising from research, it is necessary to monitor the observance of all ethical principles and codes. This study was conducted to describe the state of ethical considerations' reports in the nursing studies published by the nursing journals of Iran. Material & Methods: All the articles published by five scientific nursing journals during 2014 were selected by census and their ethical considerations' reports were assessed by a researcher made checklist. Data was analyzed by SPSS- PC and the frequency of the results was reported according to the type of the study and the published journals. Results: Among 294 reviewed articles, 128 (43.5%) reported institutional review board permission, 203 (69%) reported obtaining informed consent; 119 (58.5%) reported obtaining written consent; 87 (29.6) reported confidentiality of information and 66 (22.4%) reported the awareness of the subjects of freedom to leave the study. The assessed journals were different by the reporting of these indexes and the percentage of institutional review board permission and obtaining informed consent was higher in two journals compared with other journals. Conclusion: The findings showed that adherence to ethical considerations have been overlooked in some cases; therefore, it is necessary that the research ethics committees monitor the ethical issues more precisely during implementation of nursing studies. Also holding research workshops and the workshops on reporting the ethical observations, more emphasis on ethical guidelines in nursing journals and reviewers' attention to the ethical considerations of these journals are recommended.